Detection and Identification of Microbial Contaminant in Bakery Products in Yogyakarta City, Indonesia - Ferdian, Evelyn; Ariestanti, Catarina Aprilia; Budiarso, Tri Yahya (Universitas Kristen Duta Wacana, 2020)
Bread has been chosen as an alternative food because of its availability. In Indonesia, consumptionof breads is increased due to the change of diet pattern into packed and ready-made meals. Therefore, it isimportant to raise the awareness of bakery products quality. The purpose of this study was to detect andidentify the microbial contaminant in bakery products in Yogyakarta City, Indonesia. Bacterial coloniesfrom expired bakery products were isolated into pure isolate then confirmed by API Staph and PolymeraseChain Reaction (PCR) method. The results showed there were five kinds of gram-positive bacteria. Isolatedbacteria identified by API were Bacillus cereus (52.8%), Bacillus subtilis (97.7%), Staphylococcus aureus (97.7%),Staphylococcus epidermidis (97,9%) and Staphylococcus saprophyticus (72,2% and 61,8%).